2013
DOI: 10.1074/jbc.m113.521088
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Protein with AN1 Zinc Finger and Ubiquitin-like Domains Modulates Cdc48 (p97) Function in the Ubiquitin-Proteasome Pathway

Abstract: Background: New regulators of the ubiquitin-proteasome system (UPS) were sought in yeast. Results: Cuz1 (Cdc48-associated ubiquitin-like/zinc finger protein-1) interacts with the Cdc48/p97 ATPase and promotes endoplasmic reticulum-associated degradation. Conclusion: Cuz1 is a highly conserved Cdc48 cofactor that also binds proteasomes, especially in cells exposed to arsenite. Significance: This first characterization of the Cuz1 protein family links it to specific Cdc48/p97 complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 72 publications
3
30
0
Order By: Relevance
“…Unlike Rpn4, most proteasome subunits show long halflives, thus their levels tend to plateau or rise slowly over time. Cuz1 is a recently described arsenic-inducible proteasome-in- teracting protein that is related to the human proteasome interacting protein AIRAP (11,12). Interestingly, Cuz1 shows a more pronounced induction after arsenic treatment than a typical proteasome subunit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike Rpn4, most proteasome subunits show long halflives, thus their levels tend to plateau or rise slowly over time. Cuz1 is a recently described arsenic-inducible proteasome-in- teracting protein that is related to the human proteasome interacting protein AIRAP (11,12). Interestingly, Cuz1 shows a more pronounced induction after arsenic treatment than a typical proteasome subunit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cuz1, the other AN1 zinc finger protein, appears to function in protein degradation via direct interaction with the proteasome and Cdc48 (17,18). Cuz1 protein is specifically induced by trivalent arsenic (11,17), which is of interest because accumulating evidence suggests that a major aspect of toxicity of trivalent arsenic relates to protein misfolding (9 -11, 20).…”
Section: Dynamic Regulation Of Tmc1 Protein In Response Tomentioning
confidence: 99%
“…Previous sequence analyses suggested that TMC1 might harbor two PACE motifs in its promoter (17,18). They were both canonical PACE motifs, identical to those of well established proteasome subunits like Rpt1 and Rpn10 (Fig.…”
Section: Dynamic Regulation Of Tmc1 Protein In Response Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The 26S proteasome was the fourth protein marker. The yeast strain MHY6952 (Sa-Moura et al 2013) was grown to mid-log phase (OD 600 = 0.5) in YPD (1% yeast extract, 2% peptone, 2% dextrose) at 30°C and harvested. The cell pellet was washed once with water, frozen in liquid nitrogen, and ground in a Retsch mill according to Wälde and King (2014).…”
Section: Glycerol Gradient Sedimentation Analysismentioning
confidence: 99%